The Blood Haematology of Balitnak Native Chicken that Given Turmeric Meal - Rahim Aka; Yamin Yaddi; Hamdan Has; Sahrul Sahrul; La Ode Muh. Munadi; Rusli Badaruddin (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2022)
This study aims to examine the hematological profile of the blood of Kampung Unggul Balitnak (KUB) chickens given turmeric additives because the curcumin content in turmeric increases appetite and has antioxidant activity. The study was carried out from July to August 2021 at the Poultry Animal Science Laboratory, Faculty of Animal Science, Halu Oleo University, Kendari using a completely randomized design (CRD) with 5 treatments and 4 replications with the research sample consisting of 40 KUB chickens aged 4 months. The variables observed in the study were blood sugar levels, cholesterol levels and uric acid. The results of the study showed that the administration of turmeric flour at a level of 0.5 grams – 2 grams did not have a significant effect (P>0,5) on blood sugar, cholesterol and uric acid levels. Thus, it can be concluded that the blood hematology of superior balitnak free-range chickens with turmeric flour does not have a significant effect on blood sugar, cholesterol and uric acid.